Low levels of vitamin D are associated with multimorbidity: Results from the LifeLines Cohort Study. (18th August 2015) - Meems, Laura M. G.; de Borst, Martin H.; Postma, Dirkje S.; Vonk, Judith M.; Kremer, Hubertus P. H.; Schuttelaar, Marie-Louise A.; Rosmalen, Judith G. M.; Weersma, Rinse K.; Wolffenbuttel, Bruce H. R.; Scholtens, Salome; Stolk, Ronald P.; Kema, Ido P.; et al.
Abstract : Background. The prevalence of multimorbidity (≥ 1 disease within an individual) is rapidly increasing. So far, studies on the relationship between vitamin D and morbidity are mainly focusing on effects on single disease domains only, while vitamin D biology is associated with several diseases throughout the human body. Methods. We studied 8, 726 participants from the LifeLines Cohort Study (a cross-sectional, population-based cohort study) and used the self-developed composite morbidity score to study the association between vitamin D levels and multimorbidity. Results. Study participants (mean age 45 ± 13 years, 73% females) had a mean plasma vitamin D level of 59 ± 22 nmol/L. In participants aged between 50 and 60 years, 58% had ≥ 2 affected disease domains, while morbidity score increased with age (70–80 years: 82% morbidity score > 1; > 80 years: 89% morbidity score > 1). Each incremental reduction by 1 standard deviation (SD) of vitamin D level was associated with an 8% higher morbidity score (full model OR 0.92, 95% CI 0.88–0.97, P = 0.001). Participants with vitamin D levels < 25 nmol/L were at highest risk for increasing morbidity prevalence (versus > 80 nmol/L, OR 1.34, 95% CI 1.07–1.67, P = 0.01). Conclusions. Low levels of vitamin D are associated with higher prevalence of multimorbidity, especially in participants with vitamin D levels < 25 nmol/L. Collectively, our results favor a general, rather than an organ-specific, approach when assessing the impact of vitamin D deficiency.